TEACHING LANGUAGE THROUGH LITERATURE (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2024)
Over recent decades, much linguistic effort has been devoted to style and the teaching of literature, that is, to the pragmatic aspects of stylistic research to raise sensitivity to the use of language in literature. Literature has returned to the classroom and it is now taught again as part of language classroom activities. Increasingly, literary texts are recognised as being a medium for teaching language